HEXAMUF Interior Design Sebagai Solusi Keterbatasan Ruang Pada Kapal General Cargo - Agung Prasetyo Utomo; Septaviola Dini Utami; Rizki Aris Setyawan; Ahmad Andrei Setiawan (Departemen Teknik Kelautan Universitas Hasanuddin, 2020)
Interior design is the process of designing and planning a room by prioritizing the aspects of beauty, comfort, and function of the room. With the development of time, a room is required to provide more functions supported by adequate furnitureeven with a limited space capacity like the room on a ship. This research will design an item of furniture with a primary function and several secondary functions so that it can reduce the use of more furniture in space. This study applies anthropometric calculations to produce ergonomic furniture dimensions and is friendly to the human body shape. Besides,the design made does not leave the beauty aspect by taking a modern minimalist concept. This design takes a natural form from a beehive which is considered to have advantages in terms of structure and is easy to mix and match with oneanother. This research produces a sofa design as a primary function as a seat and bed, and a secondary function as a table and chairs. This sofa can be assembled as needed so that it gets a secondary function which is very suitable for use in a space that is not too large like the room on a tourist ship.